Determinants of profitability in Indian commercial banks - ZHANG, Gaoming (2016)
This study aims to estimate the cost efficiency as well as estimating the determinants of profitability of Indian banks during the period of 2009-2014. By utilizing accounting data of 27 commercial banks, two methods were carried out: Stochastic Frontier Analysis and System Generalized Method of Moments. Cost efficiency scores were obtained from SFA, and then input in SGMM model as an independent variable. Cost efficiency scores of Indian commercial banks in the period 2009 - 2014 were found to be 64% on average. Results from SGMM estimation suggest that banks should focus on both internal and external factors as well as efficiency scores to improve their profitability.